Silver(I) complexes of imidazolidine-2-thione and triphenylphosphines: Solid-state, solution NMR and antimicrobial activity studies. Issue 1 (2007) - Al-Zamil Al-Zamil, Norah O. Norah O.; Al-Sadhan Al-Sadhan, Khulood A. Khulood A.; Isab Isab, Anvarhusein A. Anvarhusein A.; Wazeer Wazeer, Mohamed I.M. Mohamed I.M.; Al-Arfaj Al-Arfaj, Abdul Rehman A. Abdul Rehman A.
Abstract : Mixed ligand complexes of Ag(I) with triphenylphosphine (PPh3 ), triphenylphosphine sulfide (SPPh3 ), triphenylphosphine selenide (SePPh3 ) and Imidazolidine-2-thione (Imt) have been prepared. The solution as well as solid state NMR studies have been carried out to characterize these complexes. Both solid and solution NMR show the coordination via thione group on one side and (S/Se) or PPh3 on the other side. A higher antimicrobial activity is shown by [ImtAgPPh3 ]Cl complex against gram negative Pseudomonas aeruginosa ( P. aeruginosa ) and Escherichia coli ( E. coli ) compared to the other two complexes i.e. [ImtAgSPPh3 ]Cl and [ImtAgSePPh3 ]Cl.